2016
DOI: 10.17221/419/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of potato minitubers produced in aeroponic culture

Abstract: The aeroponic system is a viable technological alternative for potato minituber production within a potato tuber seed system. The aim of the study was to evaluate the productivity of potato minitubers grown in aeroponic culture and collected in 14 successive periods of the growing season. The minitubers of cvs. Ametyst and Tajfun were tested in an experimental field after a storage period. It was found that cv. Ametyst was characterized by higher yield and number of tubers than cv. Tajfun. Yield of cv. Ametyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
5
0
7
Order By: Relevance
“…Our study is the first to our knowledge that evaluates the effect of harvesting dates in aeroponics on the dormancy period of potato minitubers. Rykaczewska (2016) observed that the yield of potato crops formed from minitubers of cv. Ametyst harvested in aeroponics responds in a quadratic form to harvesting dates.…”
Section: Dormancy Of Minitubersmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is the first to our knowledge that evaluates the effect of harvesting dates in aeroponics on the dormancy period of potato minitubers. Rykaczewska (2016) observed that the yield of potato crops formed from minitubers of cv. Ametyst harvested in aeroponics responds in a quadratic form to harvesting dates.…”
Section: Dormancy Of Minitubersmentioning
confidence: 99%
“…Minitubers of cv. Ametyst harvested at different dates had different physiological ages and varying tuber yields in the field (Rykaczewska, 2016). Therefore, there may be variation in the dormancy period of minitubers harvested at different dates, which would have implications for crop management.…”
mentioning
confidence: 99%
“…Bu sistem dünyada patates mini yumru üretim alanlarında, optimum gelişme şartlarının sağlanması yanında; toprak yapısının olumsuzluklarından etkilenilmemesi, suyun ekonomik kullanılması, yılın her mevsimi mini yumru üretim imkanı sunması ile popüler hale gelmeye başlamıştır. Son yıllarda uygun teknolojik ve otomasyon sistemlerinin kullanılması ile patates gibi iş gücü ve girdi kullanımı yüksek ürünlerde el emeği ve enerji kullanımında büyük ölçüde tasarruf edilebilmesi, diğer üretim sistemlerine göre ürünün veriminde ve kalitesinde artış görülebilmesi nedeniyle (Rykaczewska, 2016a) (Otazu, 2010). Makro ve mikro elementlerin tipi ve hangi konsantrasyon aralığında verilmesi gerektiği optimize edilmelidir.…”
Section: İd İd İdunclassified
“…Therefore, the number of seed tubers harvested from one potato plant was several times larger, which increased the net reproduction of high-value potato seed tubers (Mateus-Rodriguez et al, 2013; Basiev et al, 2019; Rykaczewska, 2016b). On average, 805 -900 mini-tubers could be picked from the area of 1 m 2 (Abdullateef et al, 2012;Rykaczewska, 2016b). Aeroponics allows researchers to develop fully automatic plant growing systems much more straightforward than substrate cultivation systems (Gabitov et al, 2018;2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of the aeroponic plant growing is atomizing the plant with a mineral-rich nutrient water solution in the closed or semi-closed environment(Martirosyan, 2014;Rykaczewska, 2016b; Wang et al, 2017).…”
mentioning
confidence: 99%